2020
DOI: 10.3390/pharmaceutics12030275
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Effects on the Release of Non-Conventional Antifibrotics from Polymer Depots

Abstract: For many chronic fibrotic conditions, there is a need for local, sustained antifibrotic drug delivery. A recent trend in the pharmaceutical industry is the repurposing of approved drugs. This paper investigates drugs that are classically used for anthelmintic activity (pyrvinium pamoate (PYR)), inhibition of adrenal steroidgenesis (metyrapone (MTP)), bactericidal effect (rifampicin (RIF), and treating iron/aluminum toxicity (deferoxamine mesylate (DFOA)), but are also under investigation for their potential po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The efficiency of an IDDS depends on its drug loading capacity, as well as on the biocompatibility and biodegradation that together contribute to the resulting drug release profile [1,9,17,[67][68][69]. In the presented work, a high PF entrapment efficiency of the PLA@PF implants (97.9 ± 13.8% of the original 500 µg PF dose per 0.3 g PLA powder)…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The efficiency of an IDDS depends on its drug loading capacity, as well as on the biocompatibility and biodegradation that together contribute to the resulting drug release profile [1,9,17,[67][68][69]. In the presented work, a high PF entrapment efficiency of the PLA@PF implants (97.9 ± 13.8% of the original 500 µg PF dose per 0.3 g PLA powder)…”
Section: Discussionmentioning
confidence: 73%
“…The efficiency of an IDDS depends on its drug loading capacity, as well as on the biocompatibility and biodegradation that together contribute to the resulting drug release profile [ 1 , 9 , 17 , 67 , 68 , 69 ]. In the presented work, a high PF entrapment efficiency of the PLA@PF implants (97.9 ± 13.8% of the original 500 μg PF dose per 0.3 g PLA powder) was achieved by co-foaming of the dry PLA and PF powders in supercritical CO 2 by the methodology proposed by us earlier [ 61 ], that allowed to bypass a problem of poor compatibility of a hydrophobic carrier material (PLA) [ 58 ] and a highly hydrophilic drug (PF) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD systems have been previously shown to enhance the solubility and bioavailability of drugs by complexing smallmolecule, hydrophobic payloads within its interior pocket, forming an 'inclusion complex' 9 . Furthermore, CD systems with high densities of neighboring inclusion complexes are able to leverage their thermodynamic interactions with the payload to yield a controlled-release delivery system that can deliver drug for 28-70 days [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…CD systems have previously been shown to enhance the solubility and bioavailability of drugs by complexing small-molecule, hydrophobic payloads within its interior pocket, forming an 'inclusion complex' [11]. Furthermore, CD systems with high densities of neighboring inclusion complexes are able to leverage their thermodynamic interactions with the payload to yield a controlled-release delivery system that can deliver drug for 28-70 days [12][13][14][15][16]. Our group has also shown that implanted cyclodextrin-based systems have the potential to 'refill' after being exposed to a second bolus dose in situ, which would present the opportunity for an adjustable and tunable window of drug delivery, as opposed to similar polymeric delivery systems which are single-use, such as PLGA [14,16].…”
Section: Introductionmentioning
confidence: 99%